The color value in the variables of scenes in the dramatic film - Abdulnaser mustafa ibrahim (مجلة فنون البصرة, 2024)
The color value in the artwork is an important thing when the artist wants to make his works of value worthy of appreciation, and there are artistic additions that increase the advantages of the artwork in form and subject matter with reference to the material, moral and expressive value of color, it is known during the filming of the film scenes that lighting has a prominent role in displaying dramatic treatments to be believable, as a change in intellectual orientations for artistic distances due to the impact on reality and imaginary, and from the standpoint of these advantages the title of the research was formed the color value in the variables of the scenes In the dramatic film, by asking the question is there a difference in value for the color variables in the scenes in the dramatic film?     From which the film (The hateful eight) was chosen to be the research sample for its prominent color connotations as a feature of the film, and therefore the research aims to shed light on the color value in the dramatic scene of the director's intellectual and aesthetic perceptions in choosing different color tones and the way they put the material and form it in an expressive language, the research followed the descriptive approach to analysis, which is consistent with the type of study by analyzing selected scenes after determining the indicators to be a tool for analysis.   So he went out.